2015
DOI: 10.1016/j.solmat.2015.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of the effect of field damping layers in quantum-dot intermediate band solar cells

Abstract: Intermediate band solar cells must demonstrate the principle of voltage preservation in order to achieve high conversion efficiencies. Tunnel escape of carriers has proved deleterious for this purpose in quantum dot intermediate band solar cells. In previous works, thick spacers between quantum dot layers were demonstrated as a means of reducing tunnel escape, but this approach is unrealistic if a large number of quantum dot layers have to be grown. In this work we report experimental proof that the use of fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In addition, for each diode a parallel resistance is considered, namely, R 3 , R 4 and R 5 . These resistances represent alternative paths for electron transitions that do not depend on the temperature and do not follow the temperature dependence established by the Shockley equation, such as a tunnel escape mechanism [29].…”
Section: Equivalent Circuit Modelmentioning
confidence: 99%
“…In addition, for each diode a parallel resistance is considered, namely, R 3 , R 4 and R 5 . These resistances represent alternative paths for electron transitions that do not depend on the temperature and do not follow the temperature dependence established by the Shockley equation, such as a tunnel escape mechanism [29].…”
Section: Equivalent Circuit Modelmentioning
confidence: 99%
“…Continuous wave (CW) spectroscopy techniques, such as photoluminescence (PL), photoluminescence excitation (PLE), and external quantum efficiency (EQE) are useful in assessing the main operating principles of these devices. In particular, they allowed us to identify the main carrier dynamics processes in the widely studied InAs/GaAs QD system, namely, tunneling and thermal escape, and to unveil the roles of WL , and trap states in the optical up-conversion mechanism. However, CW spectroscopy, based on emission or absorption, typically provides information only about the lowest-energy states involved in the interband transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although experimental observation of the second photon absorption has been observed at both low temperature [9][10][11] and room temperature, [12][13][14] the voltage preservation so far has only been shown at low temperature. 15,16 To increase the a) Now at Finisar Corporation. b) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…6 Because the thick spacer layer limited the number of QD that could be grown in the intrinsic region, Ramiro et al further improved the spacer layer design by inserting a field damping layer to reduce the electric field and observed that voltage preservation can be achieved even if tunneling exists at short circuit conditions. 16 Elborg et al experimentally revealed that a maximum in TSPA occurred at a reverse bias of À0.3 V in GaAs/AlGaAs QDSCs. 17 Creti et al demonstrated that the effect of electric field on electron-hole separation along the growth direction can be used to preserve TSPA up to room temperature.…”
Section: Introductionmentioning
confidence: 99%